2015
DOI: 10.1007/s00345-015-1626-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of metabolic syndrome and benign prostatic hyperplasia in Chinese patients

Abstract: This meta-analysis supports that the presence of MetS increases total prostate volume and annual prostate growth rate in Chinese BPH patients. Future studies are needed to explain the detailed underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
(28 reference statements)
2
29
0
1
Order By: Relevance
“…On the other hand, Zoe et al reported higher PSA levels in BPH patients with MtS (23). Our findings were not in the same line with DiBello et al (22) but, were similar with results of Zou et al (23). There was higher PSA levels in Group 1 than in Group 2 without statistical significance.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, Zoe et al reported higher PSA levels in BPH patients with MtS (23). Our findings were not in the same line with DiBello et al (22) but, were similar with results of Zou et al (23). There was higher PSA levels in Group 1 than in Group 2 without statistical significance.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have suggested that BPH may be regarded as a new aspect of MetS, and compensatory increased fasting plasma insulin is a promoter of BPH [5]. Although a positive association has been reported between MetS and prostate growth [6,7], it is not clear whether MetS may have an effect on the clinical progression of BPH. Clinical aspects including patient age, prostate volume (PV), International Prostate Symptom Score (IPSS), serum prostate specific antigen (PSA) and maximum urine flow rate (Q max ) have been identified as risk factors in the clinical progression of BPH.…”
Section: Introductionmentioning
confidence: 85%
“…There are many clinical and epidemiological studies about the relation between MetS and certain chronic diseases including BPH [11][12][13][14][15][16] . The neutrophil-lymphocyte ratio (NLR) has been proposed as an indicator of systemic inflammatory response and MetS as an indicator in some recent clinical studies [17][18][19][20] .…”
mentioning
confidence: 99%